2005
DOI: 10.1097/01.ana.0000163200.48483.56
|View full text |Cite
|
Sign up to set email alerts
|

Calculated Serum Osmolality Can Lead to a Systematic Bias Compared to Direct Measurement

Abstract: The reference method to measure serum osmolality (Mosm) is the delta cryoscopic method. However, the technology may not be available. Clinicians therefore must calculate osmolality (Cosm) as the sum of concentrations of selected principal solutes such as sodium, potassium, urea, and glucose. To evaluate the validity of Cosm in patients in hyperosmolar state we compared Cosm to Mosm. Twenty-two ICU patients treated by infusion of hypertonic solutes for intracranial hypertension following head injury were prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Among these formulas, several have been evaluated in neurological and neurosurgical patients during the administration of hyperosmolar agents [ 22 24 ]. In these studies, different formulas were used and different patients were enrolled (not treated with hyperosmolar agents [ 24 ], treated with mannitol [ 22 ] or treated with both mannitol and HS [ 23 ]). The results showed a suboptimal correlation between measured and calculated serum osmolality during mannitol administration [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these formulas, several have been evaluated in neurological and neurosurgical patients during the administration of hyperosmolar agents [ 22 24 ]. In these studies, different formulas were used and different patients were enrolled (not treated with hyperosmolar agents [ 24 ], treated with mannitol [ 22 ] or treated with both mannitol and HS [ 23 ]). The results showed a suboptimal correlation between measured and calculated serum osmolality during mannitol administration [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, different formulas were used and different patients were enrolled (not treated with hyperosmolar agents [ 24 ], treated with mannitol [ 22 ] or treated with both mannitol and HS [ 23 ]). The results showed a suboptimal correlation between measured and calculated serum osmolality during mannitol administration [ 22 , 23 ]. Although patients receiving mannitol and HS were both enrolled in the study of Vialet et al, results of mannitol and HS were not reported separately [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To maximize benefits from hypertonic saline, clinical trials and experts have reported crossing this boundary in everyday care, without complaining about an increase in grave adverse effects such as acute renal failure [18]. During such therapy, laboratory values should be monitored every 3-6 h, and meticulous attention to provide an adequate hydration status is Intracranial hypertension Himmelseher 415 [19]. Calculations consistently overestimated measured osmolalities, which led to the conclusion that direct measurements are indispensable when osmolality is checked with hypertonic saline therapy.…”
Section: Definitions and Measurementsmentioning
confidence: 99%